2022
DOI: 10.31083/j.rcm2306206
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiles of Epicardial Adipose Tissue-Derived Exosomes in Patients with Coronary Atherosclerosis

Abstract: Background and Aims: Epicardial adipose tissue, exosomes, and miRNAs have important activities in atherosclerosis. The purpose of this study was to establish miRNA expression profiles of epicardial adipose tissue-derived exosomes in patients with coronary atherosclerosis. Methods: Biopsies of epicardial adipose tissue were obtained from patients with and without coronary artery disease (CAD, n = 12 and NCAD, n = 12) during elective open-heart surgeries. Tissue was incubated with DMEM-F12 for 24 hours. Exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Similarly, elevated miR-183 levels were detected in the plasma exosome from patients with MI than in healthy individuals, which positively correlated with the degree of myocardial injury (14). Recently, Liu found that exosomal miR-183-5p from epicardial adipose tissue of patients with CAD were increased compared with those without CAD (25). Interestingly, Tong et al found that plasma miR-183-5p levels were novel diagnostic markers only for NSTEMI, but not for STEMI (15).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, elevated miR-183 levels were detected in the plasma exosome from patients with MI than in healthy individuals, which positively correlated with the degree of myocardial injury (14). Recently, Liu found that exosomal miR-183-5p from epicardial adipose tissue of patients with CAD were increased compared with those without CAD (25). Interestingly, Tong et al found that plasma miR-183-5p levels were novel diagnostic markers only for NSTEMI, but not for STEMI (15).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is to some extent consistent with other reports. It was previously proven that in patients with coronary atherosclerosis, the level of exosomal miR-485-3p derived from epicardial adipose tissue was reduced, and in ox-LDL-treated RAW 264.7 cells, miR-485-3p was significantly decreased (according to GSE99685) [ 28 , 29 ]. However, a possibly contrary finding also exists.…”
Section: Discussionmentioning
confidence: 99%
“…According to one of such studies that profiled EAT-derived exosomal miRNAs in CAD patients, 53 EAT-specific miRNAs were differentially expressed (adjusted p < 0.05, fold change > 2), of which 32 miRNAs were upregulated, while 21 of them were downregulated [ 128 ]. Among these, the increases in miR-141-3p, miR-183-5p, miR-200a-5p, miR-205-5p, and miR-429, as well as the decreases in miR-382-5p and miR-485-3p were further validated by quantitative polymerase chain reaction (qPCR).…”
Section: Micrornas Expressed In Human Eatmentioning
confidence: 99%